Essentiality of nickel in plants: a role in plant stresses - Fabiano, Caio; Tezotto, Tiago; Favarin, José Laércio; Polacco, Joseph C.; Mazzafera, Paulo (Frontiers in Plant Science, 2015)
The element Ni is considered an essential plant micronutrient because it acts as an activator of the enzyme urease. Recent studies have shown that Ni may activate an isoform of glyoxalase I, which performs an important step in the degradation of methylglyoxal (MG), a potent cytotoxic compound naturally produced by cellular metabolism. Reduced glutathione (GSH) is consumed and regenerated in the process of detoxification of MG, which is produced during stress (stress-induced production). We examine the role of Ni in the relationship between the MG cycle and GSH homeostasis and suggest that Ni may have a key participation in plant antioxidant metabolism, especially in stressful situations.